Ask a Better Question, Get a Better Answer A New Approach to Private Data Analysis - Dwork, Cynthia (11th International Conference on Database Theory (ICDT 2007), 2007)
Cryptographic techniques for reasoning about information leakage have recently been brought to bear on the classical problem of statistical disclosure control – revealing accurate statistics about a population while preserving the privacy of individuals. This new perspective has been invaluable in guiding the development of a powerful approach to private data analysis, founded on precise mathematical deﬁnitions, and yielding algorithms with provable, meaningful, privacy guarantees.